Effects of Split-Attention and Task Complexity on Individual and Collaborative Learning - John Guzmán; Jimmy Zambrano R. (MDPI AG, 2024)
School tasks often include individual and collaborative activities supported by a wide variety of learning materials. These materials can elicit varied levels of attention and learning depending on the complexity (i.e., element interactivity level) and physical separation of the information elements in the study material. The aim of this study was to explore the potential effects of the element interactivity level (i.e., high vs. low) and split attention (i.e., integrated vs. separated information) on individual and collaborative learning. An experimental design was implemented with 192 high school learners, with 64 working individually and 128 in dyads. The results revealed that in tasks with high element interactivity and integrated information, individual students learned more than groups. However, separated information benefited groups more than individual learners. It is concluded that the benefits of individual and group learning are mediated by task element interactivity and the physical separation of information sources in the study material, and recommendations for education professionals are presented.